Secondary Vapor Phase Reactions of Lignin-Derived Oligomers Obtained by Fast Pyrolysis of Pine Wood - Zhou, Shuai; Garcia-Perez, Manuel; Pecha, Brennan; McDonald, Armando; Kersten, Sascha; Westerhof, Roel (American Chemical Society, 2013)
In this paper, the effect of secondary reactions in vapor phase on the yield and composition of pyrolytic lignin (PL) oligomers was investigated. The Pine wood material was pyrolyzed at 500 °C in a fluidized bed reactor, and the vapors were transferred to a downstream tubular reactor operated at residence times between 0 and 15 s and temperatures of 400, 500, and 550 °C. Relatively small changes in yield and composition of PL oligomers were observed when the tubular reactor was operated at 400 °C. However, as the temperature in the tubular reactor increased (500 and 550 °C), the effect of residence time became more pronounced and the rate of thermal degradation of pyrolytic lignin increased. The pyrolytic lignin fraction was isolated from the bio-oil and analyzed by UV-fluorescence, TGA, Py-GC/MS, FTIR, ESI-MS, and 1H NMR. The main change observed in the composition of PL oligomers (by Py-GC/MS and 1H NMR) as a function of the vapor phase reaction time and temperature was the removal of methoxyl groups. FTIR and 1H NMR analyses indicated the formation of C double bond withO groups. The change in molecular weight distribution observed by ESI-MS suggests that both cracking and addition reactions compete during secondary vapor phase reactions in pyrolysis reactors.